Clinical indications of Drakshasava an Experiential and Scientific view - Acharya G, Shripathi; Acharya, Rajeshwari S (International Research Journal of Ayurveda & Yoga, 2021)
Asavarishta preparations are popularly used by Ayurveda physicians in the management of various disorders in modern India . Asavarishtas like Balarishta, Ashokarishta, Ashwagandharishta, Abhayarishta, Chandanasava, Chavikasava, Dashamoolarishta , Chitrakasava, Dantyarishta, Eladyarishta , Jeerakarishta , Kutajarishta , Kanakasava , Kankushthasava, Lohasava, Mustakarishta, Punarnavasava, Pushkaramoolasava , Sarivadyasava , Saraswatarishta , Usheerasava , Vidangarishta and Vasakarishta are few asavarishta formulations which are commonly used by physicians . Asavarishtas are sandhaniya preparations which are prepared by fermentation process . Since they contain 9.5 % self generated alcohol, can be preserved for prolonged period also. Drakshasava is one such preparation which is given in agnimandya , karshya, anaemia , constipation , debility, and general weakness . It is shakti vardhaka , malavatanulomana , digestive , virechana , antianaemic, rasayana , and immunomodulator , balya, brimhana , jivaniya and ojaskara also .The present paper highlights about the clinical indications of Drakshasava in and scientific and experiential view .